Reflections on Variability in the Blood–Breath Ratio of Ethanol and its Importance When Evidential Breath-Alcohol Instruments are Used in Law Enforcement - Jones, Alan Wayne; Cowan, Johnny Mack (Forensic Sciences Research, 2020)
Variability in the blood–breath ratio (BBR) of alcohol is important, because it relates a measurement of the blood-alcohol concentration (BAC) with the co-existing breath-alcohol concentration (BrAC). The BBR is also used to establish the statutory BrAC limit for driving from the existing statutory BAC limits in different countries. The in-vivo BBR depends on a host of analytical, sampling and physiological factors, including subject demographics, time after end of drinking (rising or falling BAC), the nature of the blood draw (whether venous or arterial) and the subject’s breathing pattern prior to exhalation into the breath analyzer. The results from a controlled drinking study involving healthy volunteers (85 men and 15 women) from three ethnic groups (Caucasians, Hispanics and African Americans) were used to evaluate various factors influencing the BBR. Ethanol in breath was determined with a quantitative infrared analyzer (Intoxilyzer 8000) and BAC was determined by headspace gas chromatography (HS-GC). The BAC and BrAC were highly correlated (r = 0.948) and the BBR in the post-absorptive state was 2 382 ± 119 (mean ± SD). The BBR did not depend on gender (female: 2 396 ± 101 and male: 2 380 ± 123, P > 0.05) nor on racial group (Caucasians 2 398 ± 124, African Americans 2 344 ± 119 and Hispanics 2 364 ± 104, P > 0.05). The BBR was lower in subjects with higher breath- and body-temperatures (P < 0.05) and it also decreased with longer exhalation times into the breath-analyzer (P < 0.001). In the post-absorptive state, none of the 100 subjects had a BBR of less than 2 100:1.